Borrelia burgdorferi is clonal: implications for taxonomy and vaccine development. - Dykhuizen, D E (1993)
The chromosomal genes fla and p93 and the ospA gene from a linear plasmid were sequenced from up to 15 isolates of Borrelia burgdorferi, which causes Lyme borreliosis in man. Comparison of the gene trees provides no evidence for genetic exchange between chromosomal genes, suggesting B. burgdorferi is strictly clonal. Comparison of the chromosomal gene trees with that of the plasmid-encoded ospA reveals that plasmid transfer between clones is rare. Evidence for intragenic recombination was found in only a single ospA allele. The analysis reveals three common clones and a number of rare clones that are so highly divergent that vaccines developed against one are unlikely to provide immunity to organisms from others. Consequently, an understanding of the geographic and genetic variability of B. burgdorferi will prove essential for the development of effective vaccines and programs for control. While the major clones might be regarded as different species, the clonal population structure, the geographic localization, and the widespread incidence of Lyme disease suggest that B. burgdorferi should remain the name for the entire array of organisms.